How Safety and Accessibility Affect The Perception and Local Tourist Experience?: Eastern Indonesia Marine Tourism Pre- Covid-19 Pandemic - Meyske Angel Rahantoknam (Universitas Mercu Buana, 2022)
Eastern Indonesia has enormous marine tourism potential. The main problem is accessibility. Inside the region also poses the same problem, where some local marine tourism spots can be considered accessible. In addition, the lack of infrastructure on marine tourism spots may actually have great impact on safety of tourist, which can all together affect the tourist positive experience. Based on this current condition, this study aimed to measure the impact of accessibility and safety through brand perception to tourism experience. This Study conducted In Kei Islands, which home of up and coming marine tourism spots in the country. This study used path analysis with Smart-PLS, questionnaire is used for data collection with total 120 samples. The result indicated that safety and accessibility have positive and significant effect on tourist experience, what is more, accessibility have positive and significant effect on marine tourism spot’ brand perception. This study clearly indicated that access to marine tourism spot can have a bigger impact to visitor positive experience and the brand image perception of the tourism spot, therefore tourism management with government to optimize the transportation and information related to make it easier for local, domestic and foreign tourists to visit the region.